Particle swarm optimization algorithm for permutation flowshop sequencing problem - Taşgetiren, M. Fatih; Şevkli, Mehmet; Liang, Y. C.; Gençyılmaz, Güneş (SPRINGER-VERLAG BERLIN, HEIDELBERGER PLATZ 3, D-14197 BERLIN, GERMANY, 2004)
This paper presents a particle swarm optimization algorithm (PSO) to solve the permutation flowshop sequencing problem (PFSP) with makespan criterion. Simple but very efficient local search based on the variable neighborhood search (VNS) is embedded in the PSO algorithm to solve the benchmark suites in the literature. The results are presented and compared to the best known approaches in the literature. Ultimately, a total of 195 out of 800 best-known solutions in the literature is improved by the VNS version of the PSO algorithm.
Keywords: tabu search algorithm; scheduling problems; tabu arama algoritması; çizelgeleme problemleri